Equivalent circuit method for circulating current loss of transposed strands in multi‐turn coil of a canned induction motor. Issue 8 (13th May 2019) - Wang, Dongmei; Liang, Yanping; Bian, Xu; Gao, Lianlian; Wang, Chenguang; Qiao, Xue
Abstract : For the particularity of the transposition method in large induction motor, the equivalent circuit method for the circulating current losses of the transposed strands in stator winding with multi‐turn coil is put forward. According to the unified theory of the electromagnetic field‐circuit and combining with the distribution of various leakage magnetic fields of stator winding, the general circuit network model of the stator winding is proposed, which can be applicable to different transposition angles with the consideration of the accurate distribution of leakage magnetic fields. With the basic idea of discrete points and the linearisation, the method for the leakage reactance of the transposed strands is given with an application in a 5.5 MW nuclear power pump canned induction motor, which uses the strand slot leakage reactance and the end leakage reactance to simulate the slot leakage magnetic field and the end leakage magnetic field. Through experiment, the equivalent circuit method for the circulating current losses of the transposed strands in multi‐turn coil is verified, which will provide a reference for the winding design and the winding loss calculation of the large induction motor.